Bloody tyrants & little pickles : stage roles of Anglo-American girls in the nineteenth century - Schweitzer, Marlis (Studies in theatre history and culture., 2020)
"Bloody Tyrants and Little Pickles: Anglo-American Girls on Nineteenth-century Stages traces the theatrical repertoire of a small group of white Anglo-American actresses as they reshaped the meanings of girlhood in Britain, North America, and the British West Indies during the first half of the nineteenth century. It is a study of the possibilities and the problems girl performers presented as they adopted the manners and clothing of boys, entered spaces intended for adults, and assumed characters written for men. It asks why roles like Young Norval, Richard III, Little Pickle, and Shylock came to seem "normal" and "natural" for young white girls to play and it considers how playwrights, managers, critics, and audiences sought to contain or fix the at-times dangerous plasticity they exhibited both on and offstage. Starting with but looking beyond the metropole of London where they first performed, this book follows little white girls as they traipsed across the stage in tragedies, comedies, and farces; as they transformed the pages of scientific manuals and serialized novels; as they crossed the Atlantic on board ships in service to imperial ambitions; as they modeled news forms of idealized whiteness; as their images and names repeated in objects bearing their likenesses; and as they found their way into the semi-privacy of the scrapbook and the domestic scenography of the mantelpiece"--